Model Perlindungan Hutan dengan Pendekatan Pemanfaatan HHBK bagi Masyarakat Kawasan Hutan Pendidikan UM Palangkaraya - Siti Maimunah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2017)
UMP’s University forest 4.910 ha with lowland type and peat swamp forest types habitat have many potentials of forest products especially nontimber forest product (NTFP) like latex, resin, honey, traditional medicine and ornamental plant near animal hunting (for stoping program). NTFP is one opportunity of the community to rising of economic values to make a management model for conservation base on the community with more participating to protect the forest. The research method is an NTFP inventory for 2 forest habitats to searching the market opportunity and community focus group discussion (FGD) to combine the data and community assumption. The result of this research Is we can found an effective model of forest protection with economical community participated in our forest for NTFP. NTFP potential in UMP’s University Forest is damar batu (resin), kopal damar (resin), latex of jelutung, rattan and traditional medicine. We need a more fascinating program and socialization activities for the community for other NTFP in UMP’s University Forest. The most productive of 2015-2016 is a resin of Shorea collection by the community with average 50kg/day per collector and average of community income Rp. 125.000,00/day per collector.